TINGKAT KEBERHASILAN SAMBUNGAN DAN PERTUMBUHAN BIBIT KOPI ROBUSTA (COFFEA ROBUSTA L.) HASIL GRAFTING PADA PEMBERIAN BERBAGAI JENIS MIKORIZA DAN KETINGGIAN BATANG BAWAH - Kartika, Elis (Biospecies, 2019)
The aim of this research was to obtain the mycorrhizae type and rootstockheight which was able to increase the grafting success, the growth and P uptake of grafted robusta coffee seedlings. This experiment is a two-factor factorial experiment using a completely randomized design of three replications. The first factor was mycorrhizal inoculation consisting of six levels, namely without mycorrhizal inoculation, inoculation of Glomus sp-3, Glomus sp-6, Glomus sp-15, Glomus sp-16, and mixed of Glomus sp-3, sp-6, sp-15, sp-16. The second factor is the rootstock height which consists of five levels, namely 5, 10, 15, 20 and 25 cm from base of the root. The results showed that the best growth and P uptake of grafted robusta coffee seedlings on various types of mycorrhizae were obtained at a 15 cm from the root baserootstock height. The growth and P uptake of grafted robusta coffee seedlings at rootstock heights obtained in the mixed ofGlomus sp-3, sp-6, sp-15, sp-16. The grafting success of the mycorrhizal grafted robusta coffee seedlings is 100% and the without mycorrhizal grafted robusta coffee seedlings are 79.87%, while at various rootstock heights ranges from 95.83 to 97.22%.